PELAKSANAAN ASAS AKUSATOR OLEH POLRI DALAM PENYIDIKAN TINDAK PIDANA DI POLRES DAIRI - Tioneni Sigiro; Edi Yunara; Wessy Trisna (Jurnal Mahupiki, 2018)
ABSTRACT Tioneni Sigiro* Edy Yunara** Wessy Trisna***     This thesis entitled "The implementation of the accusatory principle by the police in the investigation of crime in Polres Dairi". The principle of the accusator is a rule or norm that contains provisions that must be exercised by law enforcement officers in the case of treating suspects in their positions as human beings having dignity and dignity. A suspect must be sealed in every examination as a subject and not as an object of examination. This thesis discusses how the position of the accusator principle in the process of investigation at the police level, how the implementation of the field, and obstacles and obstacles for investigators in applying the principle. The research method used to answer these problems is empirical research method, using the approach of legislation and sociological approach. The results show that basically the application of the accusatory principle has not been fully implemented. There is an element of violence perpetrated by the police as the investigator of the suspect and there are still violations of the rights of the suspect in the examination process. Some of the obstacles encountered by the investigators in applying the accusatory principle on the investigation of the suspects are the non-professional investigators who are unprofessional in their duties, giving rise to acts contrary to the accusatory principle. In the investigation of the suspect, the investigating investigator also often finds it difficult to get information from the suspect because the suspect is silent, suddenly ill, or convoluted in giving his testimony to the investigator and not cooperating. Thus this becomes the trigger of the birth of attitudes or actions of the investigators themselves to be harsh and repressive. On the other hand, the presence of investigator supervisors is often not in accordance with the objectives that should be because of the assumptions and habits as colleagues, then the function of supervision is not going well and properly. The suggestion is that the police force, especially those in the investigation function, no longer engage in violence or threats of violence and other acts contrary to the principle of the accusator, but instead be more professional, and more innovative in finding better ways of digging information of the suspects being examined.     Keywords: Implementation, Basic Accusator, Criminal Investigation.           *Student of Faculty of Law, University of Sumatera Utara. **Lecturer at the Department of Criminal Law Faculty of Law, University of Sumatera Utara *** Lecturer at the Department of Criminal Law Faculty of Law, University of Sumatera Utara